Sleep Quality, Excessive Daytime Sleepiness, and Physical Activity Level in Health Professionals with and Without COVID-19: a Cross-Sectional Study - Neves, Ana Carolynne Santos; Chaves, Sulyvan Italo Daher; Siqueira, Pedro Paulo Simões; Alves, Karla Michelle Lima; Studart-Pereira, Luciana Moraes; Jaguaribe-de-Lima, Anna Myrna (Sleep Science, 2023)
Objective To compare the sleep quality, excessive daytime sleepiness, and physical activity level in health professionals infected and not infected with COVID-19.Methods Cross-sectional study based on online forms (Google Forms) filled out by health professionals who cared for COVID- 19 patients in hospitals in the Recife metropolitan area, Brazil, between October 2020 and May 2021. Anthropometric, sociodemographic, and occupational data were collected, along with the assessment of excessive daytime sleepiness (with Epworth Sleepiness Scale [ESE]), sleep quality (with Pittsburgh Sleep Quality Index [PSQI]), and physical activity level (with International Physical Activity Questionnaire [IPAQ] – short version).Results A total of 96 participants were assessed (37 with COVID-19, 59 without COVID-19). There were no differences between the groups regarding physical activity levels classified as sedentary, moderately active, or highly active (p = 0.850), or the weekly energy expenditure (p = 0.522). Infected professionals had a greater workload than non-infected ones, besides poorer sleep quality (10.46 ± 3.75 vs. 7.88 ± 3.75; p = 0.001) and excessive daytime sleepiness (10.19 ± 3.05 vs. 8.44 ± 3.85; p = 0.016).Conclusion Based on the results, this study shows that professionals infected with COVID-19 have poorer sleep quality, associated with excessive daytime sleepiness, in contrast with non-infected professionals.
Keywords: sleep; physical activity; health professionals; COVID-19; sleepiness